Comparative Analysis of Rest and GraphQL Technology on Nodejs-Based Api Development - Gede Susrama Mas Diyasa; Gideon Setya Budiwitjaksono; Hafidz Amarul Ma’rufi; Ilham Ade Widya Sampurno (Nusantara Science and Technology Proceedings, 2020)
Web service is a method of connecting servers and client applications. There are several types of technology in developing a web service, such as REST and Graph-QL. Graph-QL is an alternative technology created by Facebook to correct REST technology's shortcomings, especially in the data presentation section. Graph-QL provides an alternative where the client application can determine for them what data is needed. This paper analyzes the performance of the two technologies to determine which technology is suitable for their needs. The analysis carried out is to compare the response speed and data efficiency to optimize the available bandwidth. The development model uses the waterfall model, which consists of research, design, implementation, and testing. As a test object, two Node-JS based applications were developed with the Express Framework, which applied REST and Graph-QL concepts on each test object. The results obtained are that REST has better performance than Graph-QL in its response speed. On the other hand, Graph-QL also excels in data presentation by client application requests to optimize the available bandwidth.